Risk of Introduction of Infectious Animal Diseases for Europe Based on the Health Situation of North Africa and the Arabian Peninsula - Massó Sagüés, Elena; Fernández-Carrión, Eduardo; Sánchez-Vizcaíno, Jose Manuel (Frontiers in Veterinary Science, 2019)
The current growth of human population, the intensification of animal production, climate change or globalization favours an increase in the transmission of infectious diseases. Risk analysis is the tool that allows the identification of the factors involved in the introduction and the spread of infectious diseases. The main objective of this work is to evaluate the risk of entry of animal infectious zoonotic and non-zoonotic diseases from North Africa and the Arabian Peninsula to countries of the European Union. For a diseases introduction risk analysis, it has been developed probabilistic formulation to obtain the probabilities associated with each routes for each of the affected countries. The results show that, among the infectious diseases analysed in this study, avian influenza and Newcastle disease are the ones with a higher risk of entry in the European Union and the wild bird’s migration is the route with greater impact. It is confirmed a moderate probability of entry of some vector-borne diseases, bluetongue and epizootic haemorrhagic disease, through wind flow from Morocco, Algeria and Tunisia. Due to the absence of live dromedary movement to Europe, the more likely way of entry of the Middle East respiratory syndrome is through the infected people movement from Saudi Arabia, Kuwait, Qatar and Oman.